PTH-077 Geographical Mapping Of Hepatitis C Infection In North East Scotland Using A Geographical Information System (gis). (9th June 2014) - Mukhopadhya, A; Nesbit, L; Green, D; Sinclair, A-M; Dundas, P; Vijayan, B; English, S; Mcleman, L; Fraser, A
Abstract : Introduction: Chronic HCV infection affects around 37, 500 people in Scotland. A Geographical Information System (GIS) allows exploratory data analysis (EDA), mapping and visualisation of geographical data. GIS can be used to illustrate the geographical patterns and distribution of HCV infection to aid on the planning services for treatment of these patients Methods: Data was extracted from the NHS Grampian Hepatitis C database between the years 2002 to 2013 and input to the ESRI ArcGIS software. For confidentiality, each case was mapped utilising the first half of their postcodes. The Scottish Index of Multiple Deprivation was used to calculate the average deprivation score for each postcode sector. Exploratory data and statistical analysis were undertaken using Spearman's rank correlation coefficient. Results: A total of 2114 patients with hepatitis C were identified from the local NHS Grampian Hepatitis C database. The overall prevalence of hepatitis C in the Grampian region was 523 cases per 100, 000 population. The highest rate of hepatitis C was from AB11 in Aberdeen city, with 1440/100, 000 individuals. The area with the lowest occurrence was AB38 in rural Aberdeen with 21/100, 000 individuals. The higher prevalence areas corresponded to Aberdeen city and the towns of Peterhead and Fraserburgh. Outreach centres for treatment of hepatitis C were adequately stationed in high prevalence areas. The most deprived post code, AB16 in Aberdeen city, had a rate of 940/100, 000 populations. There was no statistical significance between the diagnosis of hepatitis C infection and deprivation scores of the post codes studied. There was a significant correlation between the percentage of untreated patients and average deprivation score with a correlation coefficient of -0.333 (p < 0.05). Conclusion: In this study GIS is useful to explore, visualise and present the data in a spatial context, highlighting areas with high prevalence and where individuals are being treated and where they are not. The Outreach centres were shown to be appropriately located. The higher prevalence in urban regions mirrors risk factors like drug usage in these areas. A statistically significant correlation, albeit not very high, was shown between the percentage of untreated patients and levels of deprivation. This may mean that more emphasis needs be placed on assisting those individuals who live in the most deprived areas to gain access to the treatment programmes which are available. Aberdeen Royal Infirmary is the only referral hospital for the treatment of hepatitis C and it is likely that the study underestimates the true prevalence of the infection due to a referral bias Disclosure of Interest: None Declared.